2
$\begingroup$

Given the nonhomogeneous system $\cases{ax+by+cz=d\\fx+gy+hz=k}$ with solutions $(2,-3,1)$ and the homogeneous system $\cases {ax+by+cz=0\\fx+gy+hz=0}$ with solutions $(-1,1,1),(1,0,1)$, ind the general solution of each system.

I tried plugging in the given solutions to find the relation between the variables but got confused a bit on how to finish it, plus I have no idea about the nonhomogeneous one.
Can anyone give me a clue or direct me to a more elegant way?

$\endgroup$
  • 1
    $\begingroup$ What's the confusion? $\endgroup$ – Vizag Aug 11 '18 at 19:15
0
$\begingroup$

General solution for (O)

Given (1, 0, 1), (-1, 1, 1) as solutions of (O):

$\begin{cases}{a+c=0\\-a+b+c=0}\end{cases}$

So $c=-a$ and $b=2a$ As well, we get the values of $h=-f$, $g=2f$ by same operations. Now lets arrange our system in a general form of homogeneous system $A\underline{x}=\underline{0}$:

$\begin{pmatrix} a & 2a & -a\\ f & 2f & -f \end{pmatrix}\begin{pmatrix}x\\y\\z\end{pmatrix}=\begin{pmatrix}0\\0\\0\end{pmatrix}$

$A=\begin{pmatrix}a & 2a & -a\\f & 2f & -f\end{pmatrix}$

In order for the inhomogeneous system $(M)$ to have a solution $(2, -3, 1)$, at least one of the parameters $a, f$ must not equal $0$. Assume $a\neq0$:

$\begin{pmatrix}a & 2a & -a\\f & 2f & -f\end{pmatrix}\xrightarrow{R_1=\frac{1}{a}R_1}\begin{pmatrix}1 & 2 & -1\\f & 2f & -f\end{pmatrix}\xrightarrow{R_2=R_2-fR_1}\begin{pmatrix}1 & 2 & -1\\0 & 0 & 0\end{pmatrix}$

Now we have one equation with 3 parameters, which means there are 2 free variables $y,z$ and an infinite amount of solutions. A general solution for $(O)$ looks like: $(-2t+s, t, s)$ where $t,s\in \mathbb{R}$.

General solution for $(M)$

$A\underline{x}=\underline0, \ \ \ A\underline{c}=\underline{b}\ \ \ \ \rightarrow \ \ \ A\underline{x}+A\underline{c}=\underline0+\underline{b}=\underline{b} \ \ \ \ \rightarrow \ \ \ A(\underline{x}+\underline{c})=\underline{b}$

Hence, the general solution for $(M)$ is: ${\{(2, -3, 1)+(-2t+s, t, s)|t,s \in \mathbb{R}\}}$

Another way to write the general solution: $\begin{pmatrix}2\\-3\\1\end{pmatrix}+t\begin{pmatrix}-2\\1\\0\end{pmatrix}+s\begin{pmatrix}1\\0\\1\end{pmatrix}$, $t,s \in \mathbb{R}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.